POPULIST EFFECT IN USE OF ART TO MANIPULATE FINANCIAL STATEMENT IN MFIs - Sholeh, Achmad Ridwan; Triyuwono, Iwan; Achsin, Muhammad (Profit: Jurnal Adminsitrasi Bisnis, 2018)
Creative accounting practices are shortcuts for every entity in order to achieves some special purposes. This study aimed to uncover the motives of creative accounting practices in MFIs (Self-Supporting Community Organization) Karapan Sapi. This study uses interpretive paradigm with a case study approach in order to know well the creative accounting practices that have taken place and ongoing. Based on the results of field research found that MFI Karapan Sapi do the creative accounting at UPK (Financial Management Unit). UPK is one of three units in the body of the MFI Karapan Sapi that focus in saving and loans. UPK do the creative accounting by rescheduling excessively the loan of KSM (group of creditor) in order to lower the cost of loss reserve account in income statement. Based on the field information, the motive ofÂ  creative accounting practices by UPK MFI Karapan Sapi, it showed that the UPK would like to save the allocation of loan that exist in government funding under the PNPM program and there is an indication that UPK want to pull up the image of MFI management.Â